Immune-Mediated Mechanisms of COVID-19 Neuropathology - Dunai, Cordelia; Collie, Ceryce; Michael, Benedict D. (Frontiers in Neurology, 2022)
Neurological symptoms occur in approximately one third of hospitalised COVID-19 patients1. These range from symptoms of headaches, loss of taste and smell to seizures, encephalitis, and stroke. Despite the prevalence of neurological manifestations in COVID-19 patients, scientists have struggled to find consistent evidence of direct viral invasion in neuronal tissue and CSF that can be causally attributed to these symptoms 2,3. An upregulated immune response appears to be a factor in many of the neuropathologies observed in COVID-19 patients including dysregulated cytokines, inflammation, coagulation, and the development of antibodies against self-antigens4. This review will focus on what is known and what is hypothesized about immune-mediated damage during post-acute sequelae to nervous system insult from COVID-19. However, it is outside of the scope of this review to address the likely significant heterogenous mechanisms underlying long-COVID syndrome.